Sports Education Curriculum Development Strategy in Schools: The Latest and Innovative Approach - Nur Indah Atifah Anwar (Journal Physical Health Recreation (JPHR), 2025)
This study aims to identify and analyze recent strategies in developing the Physical Education, Sports, and Health (PJOK) curriculum in schools. Using a literature review approach, the article examines innovative pedagogical models such as the Sport Education Model (SEM), Teaching Games for Understanding (TGfU), flipped classroom, gamification, and project-based learning. It also explores the integration of digital technologies and assessment approaches based on physical literacy and Outcome-Based Education (OBE). The synthesis reveals that curriculum innovation in PJOK significantly enhances student motivation, engagement, and achievement—not only in physical domains but also in cognitive and affective aspects. However, challenges such as teacher readiness, infrastructure limitations, and unequal digital access continue to hinder large-scale implementation. This review recommends stronger collaboration among educational stakeholders, teacher capacity building, and supportive policies to promote an adaptive and evidence-based PJOK curriculum.